(untitled) (Bioscience Journal, 2022)
This study aimed to empirically evaluate the adjustment quality of two stoichiometric models of methane production from diets that used different rumen fermentation modulators. We used the models proposed by Moss et al. (2000) and Blümmel et al. (1997). The data set consisted of 169 observations of in vitro methane production and volatile fatty acids (acetate, propionate, and butyrate) from dissertations, theses, and scientific articles. The model’s adequacy evaluation was only possible through combination of several statistical analyzes. The models were unable to predict the enteric methane precisely and accurately. Despite this, the model proposed by Moss et al. (2000) showed a better fit based on the mean bias (% of observed, MB), MEF, RMSEP, Cb and CCC measures compared to the model proposed by Blümmel et al. (1997). However, both models presented strong evidence against the general hypothesis H0: a = 0 & b = 1. Thus, the model proposed by MOSS et al. (2000) was more efficient, whereas the model by Blümmel et al. (1997) showed a better fit for diets with high availability of H2.